Two‐Dimensional Photosensitizer Nanosheets via Low‐Energy Electron Beam Induced Cross‐Linking of Self‐Assembled RuII Polypyridine Monolayers. Issue 28 (9th May 2022) - Küllmer, Maria; Herrmann‐Westendorf, Felix; Endres, Patrick; Götz, Stefan; Reza Rasouli, Hamid; Najafidehaghani, Emad; Neumann, Christof; Gläßner, Rebecka; Kaiser, David; Weimann, Thomas; Winter, Andreas; Schubert, Ulrich S.; et al.
Abstract: Artificial photosynthesis for hydrogen production is an important element in the search for green energy sources. The incorporation of photoactive units into mechanically stable 2D materials paves the way toward the realization of ultrathin membranes as mimics for leaves. Here we present and compare two concepts to introduce a photoactive Ru II polypyridine complex into ≈1 nm thick carbon nanomembranes (CNMs) generated by low‐energy electron irradiation induced cross‐linking of aromatic self‐assembled monolayers. The photoactive units are either directly incorporated into the CNM scaffold or covalently grafted to its surface. We characterize Ru II CNMs using X‐ray photoelectron, surface‐enhanced Raman, photothermal deflection spectroscopy, atomic force, scanning electron microscopy, and study their photoactivity in graphene field‐effect devices. Therewith, we explore the applicability of low‐energy electron irradiation of metal complexes for photosensitizer nanosheet formation. Abstract : Large area ≈1 nm thick molecular photosensitizer nanosheets are synthesized via electron irradiation induced cross‐linking of Ru II polypyridine monolayers. Their physical and chemical properties are promising for applications in two‐dimensional photocatalytic systems.